Biodegradable polyester solution and its application
By using a poly(3-hydroxy butyrate-co-3-hydroxyhexanoate) copolymer with high content of 3-hydroxyhexanoate in non-halogen organic solvents, the degradability of seawater in the prior art and the lack of seawater degradability in the prior art is solved. The problem of insufficient bonding strength achieves good solubility and high bonding strength after short-term aging.
Patent Information
- Application Number
- CN202180011515.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-29
- Filing Date
- 2021-01-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-01-14
AI Technical Summary
The prior art is difficult to provide secondary processing components with seawater degradability, and the existing adhesives may cause contamination when decompose in seawater, and the bonding strength is insufficient after aging for a short time.
By using a poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer with an average content ratio of 16 mol% or more of 3-hydroxyhexanoate has excellent solubility in a non-halogen organic solvent, and A biodegradable polyester solution with sufficient bond strength is obtained by short-term aging.
It has achieved good solubility in non-halogen organic solvents and has sufficient bonding strength through short-term aging, which solves the pollution problem caused by incomplete decomposition in seawater.
Smart Images

Figure BDA0003769613470000141
Abstract
Description
Technical Field
[0001] The present invention relates to a biodegradable polyester solution and its utilization. Background Art
[0002] A large amount of petroleum-derived plastic is discarded every year, and the shortage of landfill sites and environmental pollution caused by this large amount of waste have become serious problems. In addition, in recent years, microplastics derived from the above waste have become a major problem in the marine environment.
[0003] Polyhydroxyalkanoate resins have excellent seawater degradability and have attracted much attention as materials that can solve environmental problems caused by discarded plastics. When polyhydroxyalkanoate resins are subjected to secondary processing, adhesives, inks, coating agents, etc. ("secondary processing components") may be used. From the perspective of the above environmental issues, secondary processing components are also required to be seawater degradable.
[0004] However, such a secondary processing member having seawater degradability has not been provided so far.
[0005] As an example of a member for secondary processing having seawater degradability, for example, Patent Document 1 discloses an adhesive composition obtained by reacting a reactive monomer (for example, an acrylate monomer) with a polyhydroxyalkanoate resin.
[0006] Patent Document 2 discloses a technique for preparing an adhesive by dissolving poly(3-hydroxybutyrate-co-4-hydroxybutyrate) having a glass transition temperature Tg within a certain range in butyl acetate.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2002 / 034857
[0010] Patent Document 2: U.S. Patent No. 8283435 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, in the adhesive composition of Patent Document 1, when decomposed in seawater, the reactive monomer units flow out without being decomposed, and there is a possibility of causing marine environmental pollution.
[0013] Furthermore, the adhesive of Patent Document 2 requires aging for 24 hours or more in order to exhibit sufficient adhesive strength, and there is still room for improvement in practical use.
[0014] Therefore, an object of the present invention is to provide a biodegradable polyester solution which shows good solubility in a non-halogen organic solvent and has sufficient adhesive strength after a short period of aging.
[0015] Solution to the problem
[0016] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, for the first time found that by using a poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer (hereinafter referred to as "PHBH") having an average content ratio of 3-hydroxyhexanoate (hereinafter referred to as "3HH") within a specific range, the solubility in non-halogen organic solvents is excellent, and the biodegradable polyester solution containing the PHBH has sufficient adhesive strength even after a short period of aging, thereby completing the present invention.
[0017] Therefore, one embodiment of the present invention is a biodegradable polyester solution comprising a poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer and an organic solvent, wherein the average content ratio of 3-hydroxyhexanoate in the poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer is 16 mol% or more.
[0018] Effects of the Invention
[0019] According to one embodiment of the present invention, a biodegradable polyester solution can be provided which exhibits good solubility in a non-halogen organic solvent and has sufficient adhesive strength even after a short period of aging. DETAILED DESCRIPTION
[0020] Hereinafter, one embodiment of the present invention will be described in detail. It should be noted that, in this specification, unless otherwise specified, "A to B" indicating a numerical range means "above A and below B". In addition, all documents described in this specification are cited in this specification as references.
[0021] [1. Summary of the Invention]
[0022] A biodegradable polyester solution according to one embodiment of the present invention (hereinafter referred to as "the present biodegradable polyester solution") is a biodegradable polyester solution comprising a poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer and an organic solvent, wherein the average content ratio of 3-hydroxyhexanoate in the poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer is greater than 16 mol%.
[0023] The present inventors focused on PHBH as a seawater-degradable resin and studied related technologies for polyester solutions containing PHBH. As a result, they found that although PHBH is generally poorly soluble in organic solvents, it is soluble in small amounts in halogen organic solvents such as chloroform. However, halogen organic solvents have the problem of being harmful to human health in the operating environment.
[0024] Therefore, the present inventors conducted further research and found for the first time that the use of PHBH having an average 3HH content ratio within a specific range resulted in excellent solubility in non-halogen organic solvents. It was also found that the obtained PHBH-containing solution had sufficient adhesive strength even after a short period of aging.
[0025] Thus, for the first time, a biodegradable polyester solution is disclosed which shows good solubility in non-halogen organic solvents and has sufficient bonding strength even after a short period of aging, and the application of the present invention in various fields is extremely useful. It should be noted that, as for the so-called "good solubility" here, as an example, for example, the solubility state when the degree of turbidity is observed by the naked eye is extremely good ("◎") or good ("○") as shown in the examples described later. In addition, as for "having sufficient bonding strength even after a short period of aging", as an example, for example, as shown in the examples described later, it can be cited that the peel strength test according to the method of JIS standard Z0238 has a bonding strength of 0.1N / 15mm or more.
[0026] 〔2. Biodegradable polyester solution〕
[0027] (PHBH)
[0028] PHBH is a copolymer containing 3-hydroxybutyrate (also referred to as "3HB") and 3HH as repeating units.
[0029] In one embodiment of the present invention, PHBH can be obtained by any method such as a method of producing by microorganisms or a chemical synthesis method, without particular limitation. Among them, it is preferred that PHBH obtained by a method of producing by microorganisms is in the form of microparticles.
[0030] The microorganism producing PHBH is not particularly limited as long as it is a microorganism that can accumulate PHBH in the cell, and examples thereof include Alcaligenes such as Alcaligenes lipolytica, Alcaligenes eutrophus, and Alcaligenes latus, Pseudomonas, Bacillus, Azotobacter, Nocardia, and Aeromonas. Among them, from the viewpoint of the productivity of PHBH, strains such as Aeromonas caviae are particularly preferred, and Alcaligenes eutrophus AC32 strain into which a gene of the PHA synthase group is introduced is more preferred (Deposit No. FERM BP-6038 (transferred from the original deposit (FERM P-15786) deposited on August 12, 1998) (August 7, 2009, Patent Organism Depository of the National Institute of Advanced Industrial Science and Technology, address: 1-1-1, Central 6, Tsukuba City, Ibaraki Prefecture, Japan)) (J. Bacteriol., 179, pp. 4821-4830 (1997)). In addition, a method for obtaining PHBH from Aeromonas caviae, which is a microorganism of the genus Aeromonas, is disclosed in, for example, Japanese Patent Application Laid-Open No. 5-93049. It should be noted that these microorganisms are cultured under appropriate conditions so that PHBH is accumulated in the bacteria and used.
[0031] The carbon source and culture conditions used for the culture can be obtained by the methods described in, for example, Japanese Patent Application Laid-Open No. 5-93049 and Japanese Patent Application Laid-Open No. 2001-340078, and are not limited thereto.
[0032] The microbial produced PHBH obtained by the above method is a random copolymer. The content ratio (composition) of 3HH can be adjusted by, for example, selecting the bacterial cells, selecting the carbon source as the raw material, mixing PHBH with different 3HH compositions, mixing 3HB homopolymers, etc. For example, a method of directly using PHBH produced by bacterial cells, a method of mixing PHBH produced by multiple bacterial cells so that the average content ratio of 3HH in PHBH reaches the range given in the present invention, etc. can be cited.
[0033] The average content ratio of 3HH in PHBH is 16 mol% or more, preferably 18 mol% or more, more preferably 20 mol% or more, and particularly preferably 22 mol% or more. When the average content ratio of 3HH in PHBH is 16 mol% or more, the solubility in non-halogen organic solvents becomes good. In addition, the upper limit of the average content ratio of 3HH in PHBH is not particularly limited, but from the viewpoint of easy production, it is preferably 80 mol% or less, more preferably 65 mol% or less, and particularly preferably 50 mol% or less. It should be noted that the average content ratio of 3HH in PHBH is measured by the method described in the examples.
[0034] In one embodiment of the present invention, the weight average molecular weight (g / mol) of PHBH in the biodegradable polyester solution is, for example, 100,000 to 3,000,000, preferably 150,000 to 2,500,000, more preferably 200,000 to 2,300,000, and particularly preferably 300,000 to 2,100,000. When the weight average molecular weight of PHBH is 50,000 or more, it has the effect of showing good bonding strength. When the weight average molecular weight of PHBH is 3,000,000 or less, it has the effect of dissolving in a non-halogen organic solvent in a short time. It should be noted that for the weight average molecular weight of PHBH in the biodegradable polyester solution, a polystyrene-converted molecular weight can be obtained by using a gel permeation chromatograph (GPC) (Shodex GPC-101 manufactured by Showa Denko K.K.), using a polystyrene gel (Shodex K-804 manufactured by Showa Denko K.K.) in the chromatographic column, and using chloroform as the mobile phase.
[0035] (Organic Solvent)
[0036] In this specification, "organic solvent" is not particularly limited as long as it can dissolve PHBH well. From the viewpoint of less problems to human health in the operating environment, non-halogen organic solvents are preferred. Non-halogen organic solvents are not particularly limited, and examples thereof include ethyl acetate, butyl acetate, toluene, xylene, methyl ethyl ketone, acetone, acetonitrile, etc. From the viewpoint of good solubility in PHBH and fast drying speed, ethyl acetate, acetone, and acetonitrile are preferably used. The above organic solvents may be used alone or in combination of two or more.
[0037] (Biodegradable polyester solution)
[0038] In the present specification, the "biodegradable polyester solution" refers to a solution containing polyester decomposed by microorganisms in soil and / or seawater. The biodegradable polyester solution contains at least PHBH as a biodegradable polyester.
[0039] In one embodiment of the present invention, the solid content concentration of PHBH in the biodegradable polyester solution is, for example, 0.1 to 75% by weight, preferably 0.25 to 73% by weight, and more preferably 0.5 to 70% by weight. When the solid content concentration of PHBH is in the range of 0.1 to 75% by weight, the effect of having a viscosity suitable for processing is achieved. It should be noted that the solid content concentration of PHBH in the biodegradable polyester solution is measured by the method described in the Examples.
[0040] In one embodiment of the present invention, the biodegradable polyester solution may contain one or more biodegradable resins other than PHBH within the range of achieving the effect of the present invention. Such other resins include, for example, aliphatic polyester resins such as polybutylene succinate, polycaprolactone, and polylactic acid, and aliphatic aromatic polyester resins such as polybutylene adipate terephthalate, polybutylene sebacate terephthalate, and polybutylene azelaic terephthalate. In order to ensure the biodegradability of the biodegradable polyester solution, the addition amount of these resins is preferably 30 parts by weight or less.
[0041] In addition, in one embodiment of the present invention, the biodegradable polyester solution can include additives commonly used in the art within the scope of the present invention. As such additives, for example, inorganic fillers such as talc, calcium carbonate, mica, silicon dioxide, titanium oxide, aluminum oxide, waste paper such as rice husks, wood powder, newspapers, various organic fillers such as starch, cellulose, colorants such as pigments, dyes, odor absorbers such as activated carbon, zeolite, vanillin, dextrin and other spices, plasticizers, antioxidants, antioxidants, weather resistance improvers, ultraviolet absorbers, crystal nucleating agents, lubricants, release agents, water repellents, antibacterial agents, sliding improvers, tackifiers, fillers, chemicals, etc. The additive can include only one or more. In addition, for the solid content concentration of the additive, those skilled in the art can appropriately set it according to its purpose of use.
[0042] 〔2. Application〕
[0043] As described above, the biodegradable polyester solution shows good solubility in non-halogen organic solvents and has sufficient adhesive strength even after a short period of aging, so it can be used in various applications. Such applications are not particularly limited, and examples thereof include adhesives, binders, printing inks, coating agents, adhesives, and sustained-release processing agents. As representative examples, adhesives and printing inks are described in detail below.
[0044] (Biodegradable Adhesive)
[0045] In one embodiment of the present invention, a biodegradable adhesive comprising the present biodegradable polyester solution (hereinafter referred to as "the present biodegradable adhesive") is provided. The present biodegradable adhesive comprises a biodegradable polyester solution that exhibits good solubility in a non-halogen organic solvent and has sufficient adhesive strength even after a short period of aging, and therefore has fewer problems with human health in terms of the operating environment and is useful compared to conventional adhesives.
[0046] The solid content concentration of PHBH in the biodegradable adhesive is not particularly limited, and is, for example, 25 to 75% by weight, preferably 28 to 73% by weight, and more preferably 30 to 70% by weight. When the solid content concentration of PHBH is in the range of 25 to 75% by weight, it has an effect of having a viscosity suitable for application as an adhesive.
[0047] In one embodiment of the present invention, the biodegradable adhesive may contain various substances that can be added to a conventional adhesive within the range that does not impair its biodegradability. Such additives include, for example, colorants, fillers, plasticizers, extenders, resins, etc. The additives may contain only one or more. In addition, the solid content concentration of the additives may be appropriately set by those skilled in the art according to the purpose of use.
[0048] The bonding strength of the biodegradable adhesive is, for example, 0.1 N / 15 mm or more, preferably 1 N / 15 mm or more, when measured by the method described in the examples. When the bonding strength is 0.1 N / 15 mm or more, it has a practical strength effect as an adhesive / adhesive. In addition, the upper limit of the bonding strength of the biodegradable adhesive is not particularly limited, for example, 10 N / 15 mm or less.
[0049] (Biodegradable ink)
[0050] In one embodiment of the present invention, a biodegradable ink comprising the present biodegradable polyester solution and a pigment and / or dye (hereinafter referred to as "the present biodegradable ink") is provided. The present biodegradable ink comprises a biodegradable polyester solution that exhibits good solubility in a non-halogen organic solvent and has sufficient adhesive strength even after a short period of aging, and therefore has fewer problems with human health in terms of the operating environment, and is useful compared to conventional inks.
[0051] The solid content concentration of PHBH in the present biodegradable ink is not particularly limited, and is, for example, 0.1 to 20% by weight, preferably 0.2 to 18% by weight, and more preferably 0.5 to 15% by weight. When the solid content concentration of PHBH is in the range of 0.1 to 20% by weight, the viscosity becomes suitable for application as ink.
[0052] The pigment contained in the biodegradable ink is not particularly limited, and examples thereof include titanium oxide, calcium carbonate, barium sulfate, yellow iron oxide, carbon black, aluminum powder, mica, titanium powder, etc. These may be used alone or in combination of two or more.
[0053] The solid content concentration of the pigment and / or dye in the biodegradable ink (the weight % of the pigment / dye relative to the sum of the weight of the dye and the weight of the solvent) is not particularly limited, and is, for example, 0.1 to 20 weight %, preferably 0.2 to 15 weight %, and more preferably 0.3 to 10 weight %. When the solid content concentration of the pigment and / or dye is 0.1 weight % or more, a good coloring effect is achieved. When the solid content concentration of the pigment and / or dye is 20 weight % or less, the viscosity is adjusted to be suitable for coating.
[0054] In one embodiment of the present invention, in addition to the above-mentioned pigment and / or dye, the biodegradable ink may contain various substances that can be added to the ink in general within the range that does not impair the biodegradability. As such additives, for example, dispersants, surfactants, anti-friction agents, mildew inhibitors, preservatives, antioxidants, viscosity-increasing stabilizers, glossing agents, etc. may be cited. The additives may contain only one or more. In addition, the solid content concentration of the additives can be appropriately set by those skilled in the art according to the purpose of use.
[0055] [3. Biodegradable laminate]
[0056] In one embodiment of the present invention, a biodegradable laminate (hereinafter referred to as the "present biodegradable laminate") is provided, which comprises a biodegradable substrate and a resin layer on at least one side of the biodegradable substrate, wherein the resin layer is formed by applying the present biodegradable polyester solution to the biodegradable substrate. The present biodegradable laminate can simply impart the properties (e.g., adhesiveness) of the resin contained in the biodegradable polyester solution to the biodegradable substrate by applying the biodegradable polyester solution to the biodegradable substrate.
[0057] As a biodegradable substrate, there is no particular limitation as long as it is biodegradable and has shape retention, and examples thereof include: paper (mainly composed of cellulose), cellophane, cellulose ester; polyvinyl alcohol, polyamino acid, polyglycolic acid, pullulan, biodegradable polyester, or a substrate obtained by vapor-depositing inorganic substances such as aluminum and silicon dioxide on these substrates, etc. Among them, paper or biodegradable polyester is preferred from the viewpoint of excellent heat resistance and excellent biodegradability. The type of paper is not particularly limited, and includes paper cup base paper, plain paper, kraft paper, fully pulped paper, coated paper, tissue paper, cellophane, cardboard, etc.
[0058] Examples of biodegradable polyesters include aliphatic polyester resins such as polybutylene succinate (PBS) resins, polycaprolactone (PCL) resins, and polyhydroxyalkanoate resins, and aliphatic aromatic polyester resins such as polybutylene adipate terephthalate (PBAT) resins, polybutylene sebacate terephthalate resins, and polybutylene succinate terephthalate resins.
[0059] The type of biodegradable substrate can be appropriately selected according to the application of the present laminate. The biodegradable substrate may contain a water-resistant agent, a water-repellent agent, an inorganic substance, etc. as required, and may be a substrate surface-treated with an oxygen barrier coating, a water vapor barrier coating, etc.
[0060] The biodegradable laminate can be produced, for example, by applying the biodegradable polyester solution on one or both surfaces of the biodegradable substrate and further drying the solution as required. As such a method, any known method can be appropriately carried out without particular limitation.
[0061] [4. Method for producing laminate]
[0062] In one embodiment of the present invention, a method for producing a biodegradable laminate comprising a biodegradable substrate and a resin layer is provided, wherein the method for producing the biodegradable laminate (referred to as "the method for producing the present laminate") comprises: a coating step of applying the present biodegradable polyester solution on at least one side of the biodegradable substrate to form the resin layer. The method for producing the present laminate further comprises a drying step of drying the applied biodegradable polyester solution.
[0063] In one embodiment of the present invention, the method for producing the present laminate may include the following steps: (a) a step for producing the present biodegradable polyester solution, (b) a step for feeding the above-mentioned biodegradable substrate, (c) a step for applying the above-mentioned biodegradable polyester solution to the above-mentioned biodegradable substrate, and (d) a step for drying the above-mentioned biodegradable polyester solution after application. In addition, the method for performing each step in the method for producing the present laminate may include a step for immersing the above-mentioned biodegradable substrate in the present biodegradable polyester solution so that the present biodegradable polyester solution adheres to the surface of the above-mentioned biodegradable substrate instead of the coating step (c). The method for performing each step in the method for performing the present laminate may be appropriately performed by a known method and is not particularly limited.
[0064] The present invention is not limited to the above-described embodiments, and various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining technical means disclosed in different embodiments are also included in the technical scope of the present invention.
[0065] That is, one embodiment of the present invention is as follows.
[0066] <1> A biodegradable polyester solution comprising a poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer and an organic solvent,
[0067] The average content ratio of 3-hydroxyhexanoate in the poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer is 16 mol% or more.
[0068] <2> The biodegradable polyester solution according to <1>, wherein the organic solvent is a non-halogen organic solvent.
[0069] <3> The biodegradable polyester solution according to <1> or <2>, wherein a solid content concentration of the copolymer in the biodegradable polyester solution is 0.1 to 75% by weight.
[0070] <4> The biodegradable polyester solution according to any one of <1> to <3>, wherein the poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer has a weight average molecular weight of 100,000 to 3,000,000 g / mol.
[0071] <5> A biodegradable adhesive comprising the biodegradable polyester solution according to any one of <1> to <4>.
[0072] <6> A biodegradable ink comprising the biodegradable polyester solution according to any one of <1> to <4>, and a pigment and / or a dye.
[0073] <7> A biodegradable laminate comprising a biodegradable substrate and a resin layer on at least one side of the biodegradable substrate, wherein the resin layer is formed by applying the biodegradable polyester solution described in any one of <1> to <4> onto the biodegradable substrate.
[0074] <8> The biodegradable laminate according to <7>, wherein the biodegradable substrate is paper or biodegradable polyester.
[0075] <9> A method for producing a biodegradable laminate, the biodegradable laminate comprising a biodegradable substrate and a resin layer, the method comprising:
[0076] A coating step of applying the biodegradable polyester solution described in any one of <1> to <4> to at least one surface of the biodegradable substrate to form the resin layer.
[0077] <10> The method for producing a biodegradable laminate according to <9>, wherein the biodegradable substrate is paper or biodegradable polyester.
[0078] Example
[0079] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.
[0080] 〔Raw material resin〕
[0081] PHBH1: average content ratio 3HB / 3HH=83 / 17 (mol% / mol%), weight average molecular weight 400,000 g / mol
[0082] Manufactured based on the method described in Example 7 of WO2019 / 142845.
[0083] PHBH2: average content ratio 3HB / 3HH=76 / 24 (mol% / mol%), weight average molecular weight 560,000 g / mol
[0084] Manufactured based on the method described in Example 6 of WO2019 / 142845.
[0085] PHBH3: average content ratio 3HB / 3HH=72 / 28 (mol% / mol%), weight average molecular weight 610,000 g / mol
[0086] Manufactured based on the method described in Example 9 of WO2019 / 142845.
[0087] PHBH4: average content ratio 3HB / 3HH=72 / 28 (mol% / mol%), weight average molecular weight 2.02 million g / mol
[0088] Manufactured based on the method described in Example 9 of WO2019 / 142845.
[0089] PHBH5: average content ratio 3HB / 3HH=72 / 28 (mol% / mol%), weight average molecular weight 100,000 g / mol
[0090] Manufactured based on the method described in Example 9 of WO2019 / 142845.
[0091] PHBH6: average content ratio 3HB / 3HH=85 / 15 (mol% / mol%), weight average molecular weight 80,000 g / mol
[0092] Manufactured based on the method described in Example 4 of WO2019 / 142845.
[0093] X131A: Kaneka Biodegradable Polymer PHBH (registered trademark) X131A (Poly (3-hydroxybutyrate-co-3-hydroxyhexanoate)) manufactured by Kaneka Co., Ltd.
[0094] 151C: Kaneka Biodegradable Polymer PHBH (registered trademark) 151C (Poly (3-hydroxybutyrate-co-3-hydroxyhexanoate)) manufactured by Kaneka Co., Ltd.
[0095] 〔Measurement and evaluation methods〕
[0096] Evaluations in Examples and Comparative Examples were performed according to the following methods.
[0097] (Average content of 3HH)
[0098] 2 mL of sulfuric acid-methanol mixed solution (volume ratio 15:85) and 2 mL of chloroform were added to 20 mg of dried poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer, which was sealed and heated at 100°C for 140 minutes to obtain methyl ester as a decomposition product of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer. After cooling, 1.5 g of sodium bicarbonate was gradually added thereto for neutralization, and the mixture was left to stand until carbon dioxide gas was no longer generated. 4 mL of diisopropyl ether was added and mixed thoroughly, followed by centrifugation, and the monomer unit composition of the polyester decomposition product in the supernatant was analyzed by capillary gas chromatography.
[0099] (Solid content concentration)
[0100] The solid content concentration was calculated by the following formula.
[0101] Solid content concentration (%) = resin weight (g) / (resin weight (g) + solvent weight (g)) × 100
[0102] (Weight average molecular weight)
[0103] The molecular weight was determined as polystyrene-equivalent molecular weight using gel permeation chromatography (GPC) (Shodex GPC-101 manufactured by Showa Denko K.K.) using polystyrene gel (Shodex K-804 manufactured by Showa Denko K.K.) and chloroform as the mobile phase.
[0104] (Dissolved state)
[0105] The resin raw material was dissolved in a solvent, heated in an oven at 60° C. for 6 hours, and then the dissolved state was observed. The degree of white turbidity was visually observed and evaluated.
[0106] <Evaluation>
[0107] ◎: Very good
[0108] ○: Good
[0109] ×: Not dissolved.
[0110] (Adhesion Strength)
[0111] The biodegradable polyester solution was unbleached and applied to kraft paper (weight per unit area: 150 g / m 2 ) to form a coating layer (resin layer). Next, the coating layer was sandwiched with the same kraft paper and laminated using a roller weighing 2 kg. Then, it was heated and dried in an oven at 60°C for 1 hour, and the obtained product was used as a sample.
[0112] The sample was cut into 15 mm width according to the method of JIS standard Z0238, and the peel strength test was performed. The distance between the chucks was 100 mm and the tensile speed was 300 mm / min. The peel tester used was Shimadzu Autograph EZ-LX (manufactured by Shimadzu Corporation).
[0113] (Ink Evaluation)
[0114] The biodegradable ink drop portion of the dried sample was pressed with a finger to evaluate the ink properties.
[0115] <Evaluation>
[0116] ○: Good (the ink is not transferred to the finger side and is fixed on the paper)
[0117] ×: Defective (ink was transferred to the finger side).
[0118] [Example 1]
[0119] (Preparation of Adhesive)
[0120] PHBH1 was used as a resin raw material, and ethyl acetate was added as a solvent to prepare a solid content concentration of 30% by weight. Then, the biodegradable polyester solution adhesive was prepared by heating in an oven at 60°C for 6 hours. The state at this time was observed visually to evaluate the dissolution state of PHBH.
[0121] The prepared solution was unbleached and applied to kraft paper (weight per unit area: 150 g / m 2 ), forming a coating layer (resin layer). Next, the coating layer was sandwiched with the same kraft paper and laminated using a roller weighing 2 kg. Then, it was heated and dried in an oven at 60°C for 1 hour, and the obtained product was used as a sample to evaluate the bonding strength. The dissolved state of PHBH and the evaluation results of the bonding strength are shown in Table 1.
[0122] (Preparation of ink)
[0123] PHBH1 was used as a resin raw material, and ethyl acetate was added as a solvent to prepare a solid content concentration of 10% by weight. Then, 2 parts of titanium oxide powder were added as a pigment. Then, it was heated in an oven at 60°C for 6 hours, and the pigment was dispersed using a homogenizer to prepare a biodegradable ink.
[0124] 1 ml of the ink solution was dropped onto black paper using a dropper and dried at 60°C for 1 hour. The obtained product was used as a sample and the ink properties were evaluated.
[0125] [Example 2]
[0126] The dissolution state and adhesive strength of PHBH and ink properties were evaluated in the same manner as in Example 1 except that the raw material was changed to PHBH2. The results are shown in Table 1.
[0127] [Example 3]
[0128] The dissolution state and adhesive strength of PHBH and ink properties were evaluated in the same manner as in Example 1 except that the raw material was changed to PHBH3. The results are shown in Table 1.
[0129] [Example 4]
[0130] The dissolution state and adhesive strength of PPHBH and ink properties were evaluated in the same manner as in Example 1 except that the raw material was changed to PHBH4. The results are shown in Table 1.
[0131] [Example 5]
[0132] The dissolution state and adhesive strength of PHBH and ink properties were evaluated in the same manner as in Example 1 except that the raw material was changed to PHBH5. The results are shown in Table 1.
[0133] [Example 6]
[0134] The dissolution state and adhesive strength of PHBH and ink properties were evaluated in the same manner as in Example 1, except that the raw material was changed to PHBH3 and the solid content concentration was changed to 50% by weight.
[0135] [Example 7]
[0136] The dissolution state and adhesive strength of PHBH and ink properties were evaluated in the same manner as in Example 1, except that the raw material was changed to PHBH3 and the solid content concentration was changed to 70% by weight.
[0137] [Example 8]
[0138] The dissolution state and adhesive strength of PHBH and ink properties were evaluated in the same manner as in Example 1, except that the raw material was changed to PHBH3 and the solvent was changed to acetone. The results are shown in Table 1.
[0139] [Example 9]
[0140] The dissolution state and adhesive strength of PHBH and ink properties were evaluated in the same manner as in Example 1, except that the raw material was changed to PHBH3 and the solvent was changed to acetonitrile. The results are shown in Table 1.
[0141] [Comparative Example 1]
[0142] The dissolution state of PHBH was evaluated in the same manner as in Example 1 except that the raw material was changed to X131A. The results are shown in Table 1.
[0143] [Comparative Example 2]
[0144] The dissolution state of PHBH was evaluated in the same manner as in Example 1 except that the raw material was changed to 151C. The results are shown in Table 1.
[0145] [Comparative Example 3]
[0146] The dissolution state of PHBH was evaluated in the same manner as in Example 1 except that the raw material was changed to PHBH6. The results are shown in Table 1.
[0147] [Comparative Example 4]
[0148] The dissolution state of PHBH was evaluated in the same manner as in Example 1 except that the raw material was changed to 151C and the solvent was changed to acetone. The results are shown in Table 1.
[0149] [Comparative Example 5]
[0150] The dissolution state of PHBH was evaluated in the same manner as in Example 1, except that the raw material was changed to 151C and the solvent was changed to acetonitrile. The results are shown in Table 1.
[0151]
[0152] 〔result〕
[0153] Table 1 shows that in the examples, the dissolution state of PHBH in the non-halogen organic solvent is better than that in the comparative examples. It also shows that the biodegradable adhesive comprising the biodegradable polyester solution produced in the examples has excellent bonding strength. It also shows that the biodegradable ink comprising the biodegradable polyester solution produced in the examples has good ink properties.
[0154] This shows that the biodegradable polyester solution has good solubility in non-halogen organic solvents and has sufficient adhesive strength even after a short period of aging.
[0155] Industrial Applicability
[0156] The biodegradable polyester solution of the present invention can be suitably used in various fields including coatings, adhesives, printing inks, fiber processing, sheet / film processing, paper processing and the like.
Claims
1. A biodegradable polyester solution comprising a poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer and an organic solvent, The average content ratio of 3-hydroxyhexanoate in the poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer is 16 mol% or more and 80 mol% or less, The organic solvent is at least one selected from ethyl acetate, butyl acetate, toluene, xylene, methyl ethyl ketone, acetone, and acetonitrile. The solid content concentration of the poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer in the biodegradable polyester solution is 0.1 to 75% by weight. The weight average molecular weight of the poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer is 100,000 to 3,000,000 g / mol.
2. The biodegradable polyester solution according to claim 1, wherein The average content ratio of 3-hydroxyhexanoate in the poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer is 22 mol % or more and 80 mol % or less.
3. A biodegradable adhesive comprising the biodegradable polyester solution according to claim 1 or 2.
4. A biodegradable ink comprising the biodegradable polyester solution according to claim 1 or 2, and a pigment and / or a dye.
5. A biodegradable laminate comprising a biodegradable substrate and a resin layer on at least one side of the biodegradable substrate, The resin layer is formed by applying the biodegradable polyester solution according to claim 1 or 2 onto the biodegradable substrate.
6. The biodegradable laminate according to claim 5, wherein The biodegradable substrate is paper or biodegradable polyester.
7. A method for producing a biodegradable laminate, the biodegradable laminate comprising a biodegradable substrate and a resin layer, the method comprising: A coating step of applying the biodegradable polyester solution according to claim 1 or 2 to at least one surface of the biodegradable substrate to form the resin layer.
8. The method for producing a biodegradable laminate according to claim 7, wherein: The biodegradable substrate is paper or biodegradable polyester.
Citation Information
Patent Citations
Copolymer and its production
JP1993093049A
Method for producing polyester
JP2001340078A
PHA adhesive compositions
US8283435B2
Compositions comprising low molecular weight polyhydroxyalkanoates and methods employing same
WO2002034857A2
Biodegradable polyester resin composition and method for producing the same
JP2004161802A